Lectotypification of Cypselea meziana (Aizoaceae, Sesuvioideae) - Jocou, Adriel I.; Minué, Carlos R. (Phytotaxa, 2020)
The name Cypselea meziana was originally published by Müller (1908: 72) and recently transferred to the genus Sesuvium Linnaeus (1759: 1058) as S. mezianum (Müller 1908: 72) Bohley & G. Kadereit in Bohley et al. (2017: 138). This is an endemic Paraguayan species, represented by creeping perennial herbs, rooted at the nodes, that grows in salty soils (Bohley et al. 2017). Morphologically, S. mezianum displays a unique feature in comparison with the other perennial Sesuvium species, i.e. 3 stamens (vs. 5 or more).